2005
DOI: 10.1111/j.1365-3156.2005.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Do growth monitoring and promotion programs answer the performance criteria of a screening program? A critical analysis based on a systematic review

Abstract: Summaryobjective Growth Monitoring and Promotion programs (GMP) have been intensively promoted to improve children's health in developing countries. It has been hoped that regularly weighing children would result in the early detection of growth falterers, and that the growth chart would serve as an educational tool to make that state apparent to both health workers and caretakers in order to trigger improved caring practices. Our objective was to review whether GMP answers the theoretical grounds of a screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 83 publications
(118 reference statements)
2
32
1
3
Order By: Relevance
“…Contrary to findings from a study by [14], the study discovered that caregivers had poor participation in growth monitoring and promotion. Nevertheless, the findings were similar to the findings of a study conducted by [15] which found out that mothers in growth monitoring program have good preventive behaviour.…”
Section: Discussioncontrasting
confidence: 53%
“…Contrary to findings from a study by [14], the study discovered that caregivers had poor participation in growth monitoring and promotion. Nevertheless, the findings were similar to the findings of a study conducted by [15] which found out that mothers in growth monitoring program have good preventive behaviour.…”
Section: Discussioncontrasting
confidence: 53%
“…These practices do not enable the GMP programme to effectively improve mothers' knowledge and practices for better child growth outcomes [11,12]. The poor delivery of counselling has been attributed to a lack of required knowledge and skills on the part of health workers, heavy demand relative to personnel, lack of incentives and motivation, inadequate supervision, uncooperative and mistrusting mothers [12,27,35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Similar studies suggest that a poor understanding of the growth chart and its purpose was a major reason why the monitoring programmes failed and fell into disrepute. 5,15,22 De Onis showed that more than half of the countries evaluated by UNICEF in 1978 and in 1999/2000, experienced difficulties with the use of the RTHC. 18 Many RTHCs reflected missed immunisation opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…16 Twenty-nine per cent of healthcare workers in developing countries throughout the world have a poor understanding of the growth curve reference. 22 They seldom asked to see the RTHC, did not plot the weight of the child in the RTHC during consultations, and demonstrated poor identification of children with malnutrition whose weight remained below the third percentile over time. 3 This was observed at all levels of health care, namely primary, secondary and even tertiary.…”
Section: Discussionmentioning
confidence: 99%